Academic Senate Minutes 2022-04-28 - Academic Senate:::::::::
Agenda Approved. Minutes of 9/6/12 approved. Chair Report. President Report. Department of Intercollegiate Athletics Off Campus Test Proctoring Procedures. APC's work with Extended Education discussion. Provost Report. Trustee's Committee on Educational Policy substitute agenda item resolution creation approved. Vice Chair Report. Senate agenda approved.